IBN TAIMIYAH'S CONTRIBUTION TO ISLAMIC PHILOSOPHY OF EDUCATION: A CRITICAL REVIEW AND ITS RELEVANCE IN THE MODERN ERA - Sutiono, Sutiono; Nuro'in, Muhammad Zulfiqor; Rizaldi, Bella Mashita (Program Studi Pendidikan Agama Islam Fakultas Agama Islam Universitas Islam As-Syafi'iyah, 2025)
This article critically examines the educational philosophy of Ibn Taimiyah, a prominent Islamic scholar, focusing on his contributions to the foundation of Islamic education and its relevance in the context of contemporary challenges. Ibn Taimiyah emphasized the centrality of tawhid (monotheism) as the core of all educational efforts, aiming to cultivate individuals who are not only knowledgeable but also spiritually devoted and morally upright. Education, in his view, is a transformative process that integrates intellectual growth with ethical and religious development. He asserted that the ideal teacher must be sincere, trustworthy, and committed to guiding students toward truth, while students must approach learning with humility, respect, and the sincere intention of seeking God’s pleasure. This study also explores the applicability of Ibn Taimiyah’s thoughts in the modern era, especially in addressing the moral and spiritual crises faced by contemporary educational systems. His holistic approach—balancing religious values with the acquisition of worldly knowledge—offers valuable insights for designing character-based education today. Through critical analysis, this article concludes that Ibn Taimiyah’s educational thought provides a timeless philosophical foundation that remains relevant and can inspire modern Islamic educational reform.